History of the Farm Credit Fellows Program - Eddy LaDue (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2013)
In the spring of 1971 the College of Agriculture and Life Sciences at Cornell University, under the leadership of Director of Resident Instruction Earl Brown, was developing an undergraduate internship program. One of the institutions asked to participate in this program was the Farm Credit Banks of Springfield. After giving the request careful thought, the Farm Credit Banks of Springfield responded that the confidential and personal nature of their business did not lend itself well to short term student internships. However, if the College would like to make a different proposal that would improve the practical training and exposure of students with less focus on confidential information; they would give support of such a program careful consideration. Professor Robert Smith, with assistance from Eddy LaDue, Arthur Bratton , Clifton Loomis, Bernard Stanton, George Casler and others, developed a proposal for the Farm Credit - Cornell Study Program. The Farm Credit Banks of Springfield agreed to fund and support the program. Participants in the program were known as Farm Credit Fellows, and the program became known as the Farm Credit Fellows Program.
Keywords: 330